Reel justice in the context of teaching Legal English as a foreign language. - Dąbrowski, Andrzej (Glottodidactica, 2016)
The paper tackles the issue of law-related cinematic and television productions, metaphorically described as reel justice, in the context of teaching Legal English as a foreign language. In the light of current trends in ESP and film pedagogy, an integrated skills teaching approach is presented that attempts to invoke subject-specific, intercultural and language knowledge of Polish learners of Legal English. The core of the paper focuses on different film-based tasks, exploiting the American series Boston Legal as a didactic material. The paper concludes with recommendations for further research.